Perceived Value, Kepuasan dan Revisit Intention Wisatawan pada Lokasi Wisata - Megasari Gusandra Saragih; Bunga Aditi; Annisha Suvero Suyar (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the effect of perceived value and satisfaction on tourists' revisit intention on Merci Barn Tourism. The sampling technique used non-probability sampling with a total sample of 97 people. The data was obtained by giving a statement in the form of a questionnaire directly to the respondent to obtain valid data. Based on the results of the analysis, it is known that perceived value and satisfaction have a positive and significant influence on the revisit intention of tourists to Merci Barn Tourism, either simultaneously or partially. Determination test results found an R square value of 0.794, this means that the revisit intention of tourists to Merci Barn Tourism can be explained by the perceived value and satisfaction variables of 79.4%, while the rest (20.6%) is explained by other factors outside the model.